Pendekatan Pembelajaran Kognitif Kompleks dalam Pendidikan Agama Islam: Strategi, Tantangan dan Solusi - Hidayatul Maghfiroh; Zaenudin Zaenudin (Muaddib: Jurnal Pendidikan Agama Islam, 2025)
Effective Islamic religious education requires a learning approach that supports complex cognitive processes to address the challenges of globalization. This study aims to explore how learning approaches that support complex cognitive processes can affect students understanding and practice of Islamic teachings. The research method used is qualitative literature review, collecting and analyzing literature related to learning approaches, cognitive development, and modern challenges in Islamic education. The results indicate that methods such as group discussions, case studies, and problem-based learning (PBL) are highly effective in enhancing students critical, analytical, and reflective thinking abilities. However, challenges such as a lack of teacher competence and student resistance to interactive learning methods hinder optimal implementation. This study recommends the need for teacher training, integration of educational technology, and the creation of a conducive learning environment to overcome these challenges. The findings are expected to provide practical insights for educators, policymakers, and researchers in optimizing Islamic education in the challenging global era.